COL6A3 expression in adipocytes associates with insulin resistance and depends on PPARγ and adipocyte size. (10th April 2014) - Dankel, Simon N.; Svärd, Jessica; Matthä, Simone; Claussnitzer, Melina; Klöting, Nora; Glunk, Viktoria; Fandalyuk, Zinayida; Grytten, Elise; Solsvik, Margit H.; Nielsen, Hans‐Jørgen; Busch, Christian; Hauner, Hans; et al.
<x xml:space="preserve">Abstract</x> Objective COL6A3 may modulate adipose tissue function in obesity and insulin resistance. A role for human adipocytes linking COL6A3 with insulin resistance warrants exploration. Methods COL6A3 mRNA in abdominal subcutaneous adipose samples was compared between (1) BMI‐matched obese subjects resistant or sensitive to insulin (surgical whole tissue biopsies, n = 30/group), (2) lean/overweight and obese subjects (isolated adipocytes from collagenase‐treated surgical biopsies, n = 11/group), (3) developing primary human adipocytes with/without knockdown of the insulin‐sensitizing adipogenic gene PPARG (collagenase‐treated lipoaspirate, n = 5), and (4) small and large adipocytes from lean/overweight subjects (collagenase‐treated surgical biopsies or lipoaspirate, n = 10). Insulin resistance and sensitivity were assessed by euglycemic‐hyperinsulinemic clamp (glucose infusion rate <60 and >70 μmol kg−1 min−1, respectively) (1), or by HOMA‐IR and TG/HDL ratio (2). Results Whole tissue COL6A3 mRNA was 2.6‐fold higher in insulin resistant compared to sensitive subjects (P < 0.001). In isolated adipocytes, COL6A3 mRNA correlated positively with BMI (P = 0.007), HOMA‐IR (P = 0.039), and TG/HDL (P = 0.004). PPARG knockdown in developing adipocytes increased COL6A3 mRNA 1.5‐fold (P = 0.043). The inverse relationship with adipocyte development was further supported by 2.8‐fold higher COL6A3 mRNA in small compared to large adipocytes (P = 0.004). Conclusion Increased adipocyte COL6A3 expression associates with insulin resistance in humans, which may involve impaired PPARγ‐mediated adipocyte development.